Eficiência técnica e ambiental da pecuária leiteira na região do Triângulo Mineiro e Alto Paranaíba. - Silva, Camila Stefaní de Sousa (2017)
Milk production is one of the main economic activities in Brazil generating jobs and income to many people. According to estimates made with the Agriculture and Livestock Census 2006, this activity employs around 3.6 millions of people. In 2015, the milk production in Brazil was 35 billion liters. Among the Brazilian states, Minas Gerais stands out for being the biggest milk producer of the country, achieving 9.14 billion liters in 2015. Considering only the state of Minas Gerais, the regions “Triângulo Mineiro” and the “Alto Paranaíba” stand out, producing 25% of the amount of the whole state in the same year (2015). Given the economic importance of milk production to the country and to the regions mentioned, this work estimated a stochastic frontier production, using econometric analysis in order to evaluate the technical and environmental efficiency of the market of milk production in the regions “Triângulo Mineiro” and “Alto Paranaíba”. In order to estimate the frontiers of technical and environmental efficiency, the methodology exposed by Reinhard, Lovell and Thjssen (1999) was used, Translog and a mean inefficiency function. The data used was provided by Educampo/SEBRAE with information of 178 milk producers of the analyzed region, in 2016. The average of technical efficiency of the farms is 89% and the environmental efficiency is 73%. In addition, through Spearman's correlation, it was found that there is a positive correlation between technical and environmental technique.